12‐Year Study at Saitama Stadium 2OO2: The Relationship between Turf Quality and Rootzone Functions by Temperature‐Controlling System. Issue 1 (19th October 2017) - Tonogi, Hideaki; Wajima, Masataka
Abstract : A 12‐yr soccer pitch survey was performed at Saitama Stadium 2OO2 after opening for the Japan‐Korea World Cup in 2002. This survey lasted from 2002 to 2015 and measured traits such as ball rebound, ball roll, surface hardness, traction, ground surface hardness, grass height, infiltration rate, 50‐ and 100‐mm depth air permeability, and root length. Most notably, this paper reports on tensile strength data obtained using a new handy‐type device. This device will be useful to conduct future periodic surveys of soccer pitches easily and without expense.